Agenda 21 and prevention of sea-based marine pollution - Nollkaemper, Andre (Butterworth-Heinemann LondonGB, 1993)
Discusses some of the tasks states are confronted with in implementing Agenda 21's paragraphs on sea-based marine pollution.